2017
DOI: 10.11604/pamj.2017.28.73.12827
|View full text |Cite
|
Sign up to set email alerts
|

Tumeur glomique de la cuisse: nouveau cas et revue de la littérature

Abstract: Les tumeurs glomiques sont rares et bénignes qui se développent au-dépends du corps glomique neuromyoartériel. Si la localisation digitale est bien connue en chirurgie de la main, les localisations exradigitales souffrent d'une méconnaissance aboutissant à des erreurs diagnostiques et thérapeutiques. Nous rapportons un nouveau cas de tumeur glomique de la cuisse, et à travers une revue de la littérature, nous essayerons d'attirer l'attention vers ces localisations atypiques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The location in the thigh is unfrequent 5 . Thirty‐three cases of thigh GT have been reported in English literature 5,6,8–21 . In a series of 138 GT reported by Mravic et al, 22 11.6% cases were located in legs, but there is not specified thigh location.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The location in the thigh is unfrequent 5 . Thirty‐three cases of thigh GT have been reported in English literature 5,6,8–21 . In a series of 138 GT reported by Mravic et al, 22 11.6% cases were located in legs, but there is not specified thigh location.…”
Section: Discussionmentioning
confidence: 99%
“…5 Thirty-three cases of thigh GT have been reported in English literature. 5,6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21] In a series of 138 GT reported by Mravic et al, 22 11.6% cases were located in legs, but there is not specified thigh location. GT are usually small lesions (<1 cm) 4 but cases over 10 cm have been reported in ankle and paraspinal area by Folpe et al 8 Other thigh GT reported cases were small size lesions (between 0.5 and 3 cm).…”
Section: Clinical Evolutionmentioning
confidence: 96%
See 1 more Smart Citation
“…The search yielded 14 papers. 18,[20][21][22][23][24][25][26][27][28][29][30][31][32] Four papers (two each from Tunisia and Morocco, respectively) were excluded from the review. [29][30][31][32] The authors also made a search of the hospital pathology department database of 140,000 entries between 1992 and August 2023, for "glomus tumor" and found 43 cases, whereas the terms "glomangioma," and "glomangiomyoma" yielded two, and one patient, respectively, a total of 46 patients (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The search yielded 14 papers. 18,20–32 Four papers (two each from Tunisia and Morocco, respectively) were excluded from the review. 29–32…”
Section: Methodsmentioning
confidence: 99%